Factors Hindering Administrative Services in Malambe Village, Ponelo Islands Sub-district, North Gorontalo Regency - Ulfan N. Opi; Ellys Rachman; Tety Thalib (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This study aims to analyse what factors hinder administrative services in Malambe Village, Ponelo Islands Sub-district, North Gorontalo Regency. With the sub-focus of research, namely standard operating procedures (SOP), discipline, and facilities and infrastructure. This research uses descriptive qualitative research. The data analysis technique used is qualitative analysis technique. The results showed that the factors inhibiting administrative services in Malambe Village, Ponelo Islands Subdistrict, North Gorontalo Regency as seen from the factors of standard operating procedures (SOP), discipline, and facilities and infrastructure have not supported or hampered. This is due to the absence of a Standard Operating Procedure (SOP) information board for managing population administration, the officer in charge is not disciplined in carrying out his duties and the lack of community service facilities. The things suggested in this study are expected to the village government, in order to pay attention to obstacles that occur such as unclear standard operating procedures, low discipline, and lack of service facilities. Because these three factors, if noticed and improved, will support the implementation of service tasks.